MODEL PENDIDIKAN KARAKTER PADA SATUAN PENDIDIKAN RAUDLATUL ATHFAL (STUDI IMPLEMENTASI PENGEMBANGAN KARAKTER SEJAK USIA DINI PADA RA DHARMA WANITA KEMENAG BENGKULU SELATAN) - Sri Maryanti (UIN Fatmawati Sukarno Bengkulu, 2016)
At this time, the entire human form, not intelligence alone but the whole psychic prowess. Experts call this period as the golden age of development. Early childhood education is very important because it determines the quality of human resources in the future. This is due to the formation of the human brain is most rapid at the age when the child is at an early age. The problem in this research is how the implementation of character education, a model developed and the character values instilled in early childhood in Raudhatul RA Ministry religion Dharma Wanita South Bengkulu. This study aims to determine the implementation, the model and the value of character education in early childhood in Raudhatul Raudhatul RA RA Ministry religion Dharma Wanita South Bengkulu. This research is a field research using qualitative descriptive method. The research subject throughout the teacher / tutor in Raudhatul RA. Raudhatul RA Ministry of Dharma Wanita South Bengkulu religion which amounted to 7 people. Data collection instruments used were interviews, documentation and observation. The results showed that the implementation of character education in Raudhatul RA RA Raudhatul Dharma Wanita South Bengkulu religious ministry is carried out through three main pillars, namely the development of policies, the development of learning and partnership. The value of the characters are developed that character value in relation to God (Allah Habl min) Rated character in relation to oneself (Habl min al-nafs) Values in conjunction with other characters (Habl min al-nas wa al- bi'ah) value nationality (Habl min al-watan). Models developed in the cultivation of character is a model of collaboration and integration models ekstrakuikuler models.